The Pengaruh Strategi Pembelajaran Blended Learning terhadap Kemampuan Berpikir Kritis dan Motivasi Belajar Siswa pada Materi Reaksi Redoks - Rina Andriana; Kasmudin Mustapa; Afadil Afadil; Magfirah Magfirah (Universitas Tadulako, 2022)
Based on the results of the study, the percentage of critical thinking skills in the experimental class for each indicator namely giving simple explanations, building basic skills, concluding, making further explanations, strategies and tactics, respectively, were 82%, 63%, 72%, 68% 67%. The control class for each indicator namely giving simple explanations, building basic skills, concluding, making further explanations, strategies and tactics are 76%, 54%, 59%, 56%, 52%, respectively. The percentage results of the experimental class learning motivation questionnaire for each indicator namely attention, relevance, belief, and satisfaction respectively 84%, 83%, 87.4%, 83%, the control class for each indicator namely attention, relevance, belief, and satisfaction are 76.3%, 81%, 77%, 74.4% with the result that the blended learning strategy affects critical thinking skills and learning motivation of class X students on redox reaction material at SMAN 1 Balaesang.